Pengaruh Pengetahuan Wajib Pajak, Sanksi Pajak Dan Kualitas Pelayanan Perpajakan Kepatuhan Wajib Pajak UMKM Di Kota Padang - Kusufiyah, Yunita Valentina; Putri, Resti Ramadhani; Anggraini, Dina (CV. ITTC INDONESIA, 2024)
Revenue from the tax sector is the largest revenue compared to revenue from other sectors in Indonesia. The contribution of taxes to total state revenue averages more than 70 percent each year. The importance of tax contributions to national income greatly impacts the smooth running of government administration and the country's economy. The importance of tax revenue for the Indonesian state encourages the government to issue various policies to improve taxpayer compliance. Taxpayer compliance is an obligation that must be owned by taxpayers because taxes are a source of state revenue (Serliati & Febrianti, 2020). Increasing taxpayer compliance will increase state revenue. The purpose of this study is to see the factors that influence taxpayer compliance, especially MSME taxpayers, including: taxpayer knowledge, tax sanctions, and the quality of tax services. This study uses a quantitative approach with a population of individual taxpayers conducting Small, Micro and Medium Enterprises (MSMEs) in Padang City who have a Taxpayer Identification Number (NPWP). The results of hypothesis testing in the study prove that mandatory knowledge, tax sanctions and the quality of tax services affect the compliance of MSME taxpayers in Padang City.